Moral and Political Ideology in Georgi Markov’s Sharp Criticism of Bulgarian Totalitarianism - Dell’ Agata, Giuseppe (Sledva : NBU Journal of Humanities and Arts, 2020)
The task of this text by the is to outline the main political and ethical ideas that Georgi Markov (Bulgarian writer and dissident, murdered in exile by the Secret Services) maintains in his constant and often radical criticism towards Bulgaria regime during the years. Italian professor Giuseppe Dell’ Agata’s main point is related to Markov’s unshattered conviction that the Bulgarian regime created by the Communist Party had nothing to do with the communism or the socialism but was simply an example of state capitalism.